2020
DOI: 10.17576/ajag-2020-13-03
|View full text |Cite
|
Sign up to set email alerts
|

What Determines Executives’ Remuneration in Malaysian Public Listed Companies?

Abstract: This paper examines the impact of executives' ownership, firm profitability, board size and its components, as well as some other financial factors, on executives' remuneration in the context of Malaysia. Using a sample of 2403 firmyears during 2006-2014 among listed companies in Bursa Malaysia, the findings show that firm profitability, leverage and number of non-executive directors have negative effects on executives' remuneration. Conversely, dividends, percentage of executives' directors, board size and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…These inconsistencies extend to the outcomes of similar studies in Malaysia; for instance, Ibrahim et al (2005) found no association between firm performance and board compensation, using the data of Malaysian companies between 1998 and2001. Similar results were found by Ghasemi and Ab Razak (2020), who analyzed the data of 267 companies between the period of 2006 to 2014, to examine the association between firm profitability (measured by Return on Assets (ROA) and Return on Equity (ROE) and executive directors' compensation. The results show that firm profitability has no relationship with executives' remuneration.…”
Section: Introductionsupporting
confidence: 64%
“…These inconsistencies extend to the outcomes of similar studies in Malaysia; for instance, Ibrahim et al (2005) found no association between firm performance and board compensation, using the data of Malaysian companies between 1998 and2001. Similar results were found by Ghasemi and Ab Razak (2020), who analyzed the data of 267 companies between the period of 2006 to 2014, to examine the association between firm profitability (measured by Return on Assets (ROA) and Return on Equity (ROE) and executive directors' compensation. The results show that firm profitability has no relationship with executives' remuneration.…”
Section: Introductionsupporting
confidence: 64%
“…For the case of family-owned firms, Jaafar et al (2012) found a significant positive relationship between the CEO's pay and the firm's performance. Nevertheless, the research results of Ghasemi and Ab Razak (2020) showed that there was no significant relationship between a firm's profitability measured by ROA and ROE and executives' remuneration, which signified a weak contractual agreement in the Malaysian market in resolving agency conflict by tying directors' remuneration to firm's performance. Jong and Ho (2020) also did not find a link between an executive's remuneration and a firm's accounting performance (ROA (-1)) and stock performance (SR (-1)) for their samples of Malaysian-listed family-owned firms from 2010 to 2014.…”
Section: Baseline Results For Hypothesis H1mentioning
confidence: 95%
“…Evidence from Malaysia regarded as an expropriation of minority shareholders' interests; however, mitigated by an improved firm's performance. Nevertheless, in a study by Ghasemi and Ab Razak (2020), there was an insignificant impact of executives' ownership on their remunerations. The findings showed that both the family CEOs and family ownership had a significant positive impact on directors' remunerations (via the pay-performance nexus), implying that family directors (founder-CEOs in this study) influenced their remunerations via directorship as well as concentrated ownership.…”
Section: The Interaction Effect Of Founder Ceo's Power For Hypothesis H2mentioning
confidence: 92%
“…This, indeed, may deteriorate firms performance and thus increase the cost of debt financing. Ghasemi and Ab Razak (2020) and Lee and Chen (2011) argue that, due to ownership concentrations, CEOs with high levels of ownership may positively impact on the amount of remuneration assigned for executives in Malaysian listed companies. CEO ownership is measured by the percent of total shares owned by the CEO to total number of shares outstanding.…”
Section: Experimental Variablesmentioning
confidence: 99%